Pain between Psyche and Soma in Uro-Andrology - Pruneti, Carlo; Guidotti, Sara (International Journal of Pain Management, 2020)
How to define pain? One of the most accredited definition is certainly “An unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage" (IASP (International Association for the Study of Pain - 1986) and World Health Organization (WHO) 1. However, what are the essential components of pain experience? Certainly many factors are involved such as, among others: Perceptual ability / suitability / subjective threshold; The "subjective" experience; Multidimensionality; Occasionally or chronicity. All these components have to be taken into consideration in the treatment of these disorders which, very often, require a multidisciplinary approach. From a clinical psychological point of view, much can also be offered at a diagnostic level, from the reception to listening to the patient's suffering, to the evaluation with standardized tests and psychophysiological analysis procedures in order to arrive at an effective personalization of treatments
Keywords: Pain; Chronicity; Uro-Andrology; Tissue Damage; Multidisciplinary Approach